Systemic Administration of the Cyclin‐Dependent Kinase Inhibitor (S)‐CR8 Selectively Reduces Escalated Ethanol Intake in Dependent Rats. (30th August 2019) - Goulding, Scott P.; de Guglielmo, Giordano; Carrette, Lieselot L.G.; George, Olivier; Contet, Candice
Abstract : Background: Chronic exposure to ethanol (EtOH) and other drugs of abuse can alter the expression and activity of cyclin‐dependent kinase 5 (CDK5) and its cofactor p35, but the functional implication of CDK5 signaling in the regulation of EtOH‐related behaviors remains unknown. In the present study, we sought to determine whether CDK5 activity plays a role in the escalation of EtOH self‐administration triggered by dependence. Methods: We tested the effect of systemically administered (S)‐CR8, a nonselective CDK inhibitor, on operant responding for EtOH or saccharin, a highly palatable reinforcer, in adult male Wistar rats. Half of the rats were made EtOH‐dependent via chronic intermittent EtOH inhalation (CIE). We then sought to identify a possible neuroanatomical locus for the behavioral effect of (S)‐CR8 by quantifying protein levels of CDK5 and p35 in subregions of the extended amygdala and prefrontal cortex from EtOH‐naïve, nondependent, and dependent rats at the expected time of EtOH self‐administration. We also analyzed the phosphorylation of 4 CDK5 substrates and of the CDK substrate consensus motif. Results: (S)‐CR8 dose‐dependently reduced EtOH self‐administration in dependent rats. It had no effect on water or saccharin self‐administration, nor in nondependent rats. The abundance of CDK5 or p35 was not altered in any of the brain regions analyzed. In the bed nucleus of the stria terminalis, CDK5 abundance was negatively correlated with intoxication levels during EtOH vapor exposure but there was no effect of dependence on the phosphorylation ratio of CDK5 substrates. In contrast, EtOH dependence increased the phosphorylation of low‐molecular‐weight CDK substrates in the basolateral amygdala (BLA). Conclusions: The selective effect of (S)‐CR8 on excessive EtOH intake has potential therapeutic value for the treatment of alcohol use disorders. Our data do not support the hypothesis that this effect would be mediated by the inhibition of up‐regulated CDK5 activity in the extended amygdala nor prefrontal cortex. However, increased activity of CDKs other than CDK5 in the BLA may contribute to excessive EtOH consumption in alcohol dependence. Other (S)‐CR8 targets may also be implicated. Abstract : Cyclin‐dependent kinase 5 (CDK5) signaling regulates cellular and behavioral responses to psychostimulants and opioids. Here, we show that (S)‐CR8, a non‐selective CDK inhibitor, reduces escalated alcohol intake in a rat model of alcohol dependence. Alcohol dependence did not upregulate CDK5 in the extended amygdala or prefrontal cortex but increased CDK substrate phosphorylation in the basolateral amygdala. Altogether, these findings suggest that CDKs other than CDK5 may contribute to addiction‐related neuroplasticity.